Grain size and mineralogical constraints on leaching in the bottom ashes from municipal solid waste incineration: a comparison of five plants in northern Italy - Mantovani, Luciana; De Matteis, Chiara; Tribaudino, Mario; Boschetti, Tiziano; Funari, Valerio; Dinelli, Enrico; Toller, Simone; Pelagatti, Paolo (Frontiers in Environmental Science, 2023)
Bottom ash (BA) from municipal solid waste incinerator (MSWI) are currently classified by the European Waste Catalogue as industrial non-hazardous waste. To promote their reuse, identification and characterization of the heavy metals bearing phases (both glass and minerals), as well as their weathering behavior must be addressed for what concern the chemical composition, mineralogical phases and in high concentrations and pollutants’ mobility. An important point is weather the results from a given plant can be generalized. In this work BA from 5 northern Italy Waste to Energy (WtE) plants were sorted based on different grain sizes. The input waste of the plants is similar, coming from a culturally homogeneous area, and with similar collection management. For each grain size, a mineralogical, chemical and physical characterization has been done using of XRF, XRD, TGA and leaching test. We found that for major elements the average chemical composition of the incinerators is similar, with some difference in minor elements. Ferrara (FE) and Forlì-Cesena (FC) BA show portlandite, higher ettringite and lower amorphous than the Torino (TO) Parma (PR) and Piacenza (PC) ones. This affects the pH and the release and toxicity of the leachates. In FE and FC ashes ettringite is not dissolved, and we have low sulphate, but also Ni and Ba beyond reglementary limits, suggesting that Ni and Ba are present as hydroxides with portlandite, which dissolves. In TO, PR and PC Cr and sulphates are beyond limits, suggesting that Cr comes from dissolution in ettringite. Cu and Cl are always beyond limits; the dissolution of chlorides accounts just for 30-35% of the global Cl leachate. We observe that in the assessment of potential toxicity of the ashes mineralogy has an effect higher than the bulk chemical composition. Grain size sorting, although useful together with other techniques is not by itself able to comply with the PTE risk level. The findings contribute to the development of efficient treatment strategies of BA highlighting the need for a more thorough investigation to understand composition and properties and to find innovative ways to reuse, promoting the circular economy and sustainable waste management practices.